Perlindungan Hukum Terhadap Suami yang Menjadi Korban KDRT yang Dilakukan oleh Istri Ditinjau dari Hukum Pidana - Lubis, Rafnila; Kusbianto, Kusbianto; Sitompul, Ariman (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to evaluate the implementation of legal protection for husbands who become victims of Domestic Violence (DV) committed by their wives, with a case study in Medan City. The research focuses on the application of Law Number 23 of 2004 concerning the Elimination of Domestic Violence, the motives of wives as perpetrators, and the legal protection provided to husbands as victims. Using a normative approach, this study relies on secondary data from legislation, legal doctrines, and relevant case analyses. The findings show that Law Number 23 of 2004 explicitly provides legal protection for all DV victims, regardless of gender, including husbands. The law guarantees victims’ rights to physical protection, legal assistance, healthcare, and social rehabilitation. The motives of wives committing DV against their husbands may include dominance, frustration, revenge, or economic stress. In some cases, such acts arise from attempts to control the partner or express unresolved emotional distress. The analysis of household dynamics reveals that power imbalance, unresolved conflicts, and past trauma are common triggers of violent behavior. Legal frameworks ensure husbands’ rights to report violence and access protection and rehabilitation services. Law enforcement agencies and relevant institutions such as the Witness and Victim Protection Agency (LPSK) and the Integrated Service Center for the Empowerment of Women and Children (P2TP2A) play an essential role in guaranteeing that male victims receive appropriate and equitable protection under the law.